IoT monitoring system for air quality assessment and collecting data - Mustapha Si Tayeb; Mohamed Anis Benallal; Mohammed Salim Benabadji; Amine Houari (Indonesian Journal of Electrical Engineering and Computer Science, 2022)
The composition of the air has been visibly altered as a result of human activity, resulting in what we term air pollution. It is no longer necessary to prove the effects on ecosystems and human health. Under these conditions, governments all around the world are working to address this issue, notably in the area of real-time air quality monitoring. The implementation of a data provider is a necessary step in achieving this goal. In that case, this study presents a hardware and software solution to provide a low-cost deployable device to acquire environmental data related to AP such as CO, CO2, NH3, and NO2, along with temperature and humidity. In addition to an user interface development, a complete circuit layout and a set of software criteria are set up to ensure a reliable implementation, data collection, and network communications. The results demonstrated that the device is capable of effectively obtaining real-time data. The analysis results indicate a link between environmental conditions and parameter values. This system deployment will ultimately contribute to providing a more elaborate mapped data distribution, according to a better understanding of our environment.